Psychological training for the stimulation of resilience in the national table tennis team /Entrenamiento psicológico para la estimulación de la resiliencia en el equipo nacional de tenis de mesa. - Mónica Huie Martínez; Marta Cañizares Hernández; María del Rosario Martínez Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The present work corresponds to the research carried out on psychological resilience in athletes of the national Table Tennis team and with the theme of High Performance Sports. Its objective was to elaborate a proposal for a psychological training program to stimulate resilience in athletes of the U-18 and U-21 categories of the national table tennis team. The need to conduct studies that explore resilience in the field of Sport Psychology reveals the importance and timeliness of the topic, due to the contribution of this capacity to the performance of athletes during the training and competition process. In order to fulfill the research objective, methods from the theoretical level such as analysis and synthesis and from the empirical level, observation, interview, as well as the Resilience Scale and the Stress Coping Questionnaire were used. The main results made it possible to confirm the presence of medium and high levels of psychological resilience in the athletes studied, it was identified the protective and risk factors that influence the coping with life events and stressful situations. In addition, they made possible the elaboration of the psychological training program proposal, in correspondence with the findings. The program proposal consisted of 16 sessions, aimed at stimulating psychological resilience in the national table tennis team; it was submitted to the criteria of 11 specialists for the evaluation of its design, feasibility and usefulness, where it was highly valued by them.